1996
DOI: 10.1577/1548-8659(1996)125<0104:msfhlf>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Stream Fish Habitat Limitations from Wedge-Shaped Patterns of Variation in Standing Stock

Abstract: A wedge-shaped pattern of variation in stream fish standing stock estimates relative to a habitat variable, in which range of standing stocks increases as a function of the variable, is consistent with the concept that the habitat variable is a limiting factor for fish populations. This pattern of variation complicates interpretation of parameter estimates and significance of ordinary least-squares (OLS) regression models of conditional mean standing stock; slopes of these regression models may have little or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 35 publications
6
96
0
Order By: Relevance
“…A regression model with heterogeneous variances implies that there is not a single rate of change that characterizes changes in the probability distributions. Focusing exclusively on changes in the means may underestimate, overestimate, or fail to distinguish real nonzero changes in heterogeneous distributions (Terrell et al 1996;Cade et al 1999).The Dunham et al (2002) analyses relating the abundance of Lahontan cutthroat trout (Oncorhynchus clarki henshawi) to the ratio of stream width to depth illustrates the value of the additional information provided by quantile regression (Figure 1). The ratio was used as a predictor variable because it was an easily obtained measure of channel morphology that was thought to be related to the integrity of habitat in small streams like those typically inhabited by cutthroat trout.…”
mentioning
confidence: 99%
“…A regression model with heterogeneous variances implies that there is not a single rate of change that characterizes changes in the probability distributions. Focusing exclusively on changes in the means may underestimate, overestimate, or fail to distinguish real nonzero changes in heterogeneous distributions (Terrell et al 1996;Cade et al 1999).The Dunham et al (2002) analyses relating the abundance of Lahontan cutthroat trout (Oncorhynchus clarki henshawi) to the ratio of stream width to depth illustrates the value of the additional information provided by quantile regression (Figure 1). The ratio was used as a predictor variable because it was an easily obtained measure of channel morphology that was thought to be related to the integrity of habitat in small streams like those typically inhabited by cutthroat trout.…”
mentioning
confidence: 99%
“…Unfortunately this is a common problem with ecological data. For example, Terrell et al (1996) evaluated 35 datasets of stream fish standing stock and found that 13 violated the assumption of homoscedastic error variance required for leastsquares regression. Regression quantiles are also capable of modelling variability in the response distribution through the estimation of a range of quantiles.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, least-squares modelling techniques that estimate changes through the centre of the response will consistently underestimate the potential response to the habitat factors considered in the model, and provide only the general direction and shape of the response. A number of methodologies have been explored that are capable of describing the upper bounds of scatterplots, and include partitioned regression (Thomson et al 1996) and regression quantiles (Terrell et al 1996, Cade et al 1999. Whilst still in the developmental stage, Terrell & Carpenter (1997) call for the use of such techniques to improve the efficacy of HSI models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most contaminants interact with the soil physiochemical structure to a different extent which modifies their influence on soil respiration. As a result of these complex interactions, bivariate scattergrams of soil respiration values versus contaminant concentrations often display a characteristic 'wedge-shape' pattern that suggests contaminants act to limit maximum respiration values (32). the same dose-response curve was obtained when the influence of ni-solutions with different concentration was evaluated (16).…”
Section: ±3mentioning
confidence: 97%